Electrochemical Decarboxylative Coupling of N‐Substituted Glycines under Air: Access to C3‐Aminomethylated Imidazo[1, 2‐a]pyridines. Issue 14 (30th June 2022) - Li, Sifeng; Li, Xingchen; Wang, Taimin; Yang, Qingjing; Ouyang, Zijun; Chen, Jieyu; Zhai, Hongbin; Li, Xiao; Cheng, Bin
Abstract: An electrochemical decarboxylative aminomethylation reaction of imidazo[1, 2‐ a ]pyridines with various N ‐substituted glycines in acetonitrile at room temperature has been described. The reaction could be conducted under light‐free, catalyst‐free, oxidant‐free, and air conditions, affording the C3‐aminomethylated imidazo[1, 2‐ a ]pyridines in good to high yields. Remarkably, N ‐aryl, N, N ‐dialkyl, and N ‐alkyl‐ N ‐aryl glycines are all well‐tolerated in this easily handled protocol, which further expands the chemical space of bioactive imidazo[1, 2‐ a ]pyridine derivatives. Abstract :